Extração, caracterização e produção de biodiesel a partir do óleo da semente da planta amazônica Pachira aquática Aublet - Matsuda, Gabriel (2020)
Oils and fats are hydrophobic substances that can originate from plants or animals, formed by esters of triacylglycerols, which are products from transesterification. They are presented in a liquid and viscous state when used in environments of normal temperatures and pressures. Its extraction process usually occurs through pressing or solvent extraction. The most well-known and used vegetable oils are soy, cotton, palm oil and corn oils. Pachira Aquatica Aublet or munguba, chestnut-of-maranhão as it is known, is a tree used for afforestation of environments and has an edible seed widely used by the Amazonian population. In this sense, the objective of this work was to carry out the extraction and characterization of the oil and to verify the viability of the production of methyl esters from munguba oil. For that, the oil was extracted by two different systems, the Tecnal Fat Determinator and by the Marconi Fat Extractor and after that stage the oil started to be analyzed for its characteristics. The analyzes made for the characterization were regarding the saponification index (180.95 mg. KOH g-1 ), peroxide index (0.994 meq.Kg-1 ), acidity index (3.283 mg KOH / g), refraction index (1.4656) and the water content (2.1%), besides having considered the oil as saturated doing so, with the molecules have a greater capacity of connection between them and in mild temperatures, solidifying and becoming a fat.After the physical-chemical analysis of the oil, the biodiesel production process took place, using methanol, chloroform and sulfuric acid, afterwards the characterization of some biodiesel parameters, the kinematic viscosity at 40ºC (7.44 mm² /s), the content of water (192), specific mass at 20ºC (901.9 Kg /m³) and the esters produced,Methyl Palmitate (64.1%), Methyl Stearate (3.9%), Methyl Oleate (12.2%), and Methyl Linoleate (8.3%). The results showed that the extraction system by the Tecnal brand extractor was more efficient than the other, with a lipid content of 43.14%, and in the end the lipid content found in the munguba was 42.19%. With regard to biodiesel, the process that took place at a temperature of 60ºC and using an amount of 0.6 ml of sulfuric acid had a yield of 89.44%. The results found in the physical-chemical analyzes show that the oil, besides being used in the food industries, can be used for the production of biofuels. If there is a munguba to use for the production of biodiesel in places where there are temperatures, as in Brazil, it must be used together with an additive.